Dietary Habits, Obesity and Elevated Blood Pressure among Workers of the College of Health Sciences - Ansong, J. (University of Ghana, 2009)
Obesity and elevated blood pressure are important risk factors associated with cardiovascular diseases, type II diabetes and some cancers. These risk factors were in the past associated with affluence and developed countries. However, recent studies have shown their increasing prevalence in developing countries. Health workers influence behaviour and people who work in health worker training environment are expected to know and practice ̳healthy‘ behaviours. The study therefore sought to describe the dietary habits of workers of the College of Health Sciences (CHS) and to determine nutrition knowledge, levels of obesity and elevated blood pressure among them. This was a cross sectional study. Participants were selected by a simple random method from among 7 institutions in the CHS. Participants were interviewed using a structured questionnaire that collected information on the socio-demographic characteristics, dietary intake, anthropometric indices and blood pressure. Overweight and obesity was determined using body mass index (BMI) and waist to hip ratio (WHR). The cutoffs used were: (BMI greater than 25kg/m 2 and BMI of 30kg/m 2 for overweight and obesity respectively and waist-to-hip ratio (WHR) ≥ 0.85 for females and WHR ≥ for 0.90 for males). Elevated blood pressure was determined as systolic blood pressure greater than or equal to 140 mmHg and diastolic blood pressure greater than or equal to 90mm Hg. Data from 141 respondents were included in the analysis. This included 73 (51.8%) junior staff, 40 (28.4%) senior staff and 28 (19.9%) senior members. There were 95 males (67.4%) and 46 females (32.6%). The mean age of the study population was 40.5 ± 10.8 years. Dietary knowledge scores of majority of respondents were below the overall average score of 5.2 ± 3.2 out of an expected total 15.0. Overall, 12.8% of respondents were obese and 30.5% were overweight. The proportions of overweight and obesity were higher among junior staff (11.3% for overweight and5.0% for obesity respectively) and senior staff (11.3% for overweight and 4.3% for obesity respectively) compared to senior members (7.8% for overweight and 3.5% for obesity respectively). There were significant differences among staff categories with regards to obesity (p<0.00). However differences among staff categories with regards to overweight was not significant (p<0.42). Elevated blood pressure was more common among junior staff (18.4%) and senior staff (10.6%) compared to senior members (8.5%). The differences among staff categories was also significant (p<0.02). In conclusion, the high prevalence of obesity in the studied workers‘ sample, suggest that workers would benefit from a nutrition and health program to make them well informed on issues relating nutrition knowledge so as to make healthy food choices and to improve their eating habits. Regarding elevated blood pressure, there is the need to introduce health education measures that will promote prevention and early detection of hypertension and encourage better compliance to treatment.
Thesis (MPH)-University of Ghana